Accelerating Innovation: Design, Development, and Manufacturing of Artificial Intelligence- Enhanced Smart Electric Vehicles - Kamlesh Mahajan; Ravikant Nanwatkar; Aditya Kulkarni; Abhishek Deshmukh; Harshad Bhosale; Vaibhav Vanjari (International Journal of Manufacturing and Production Engineering, 2025)
This research paper delves into the dynamic landscape of automotive engineering, focusing on the accelerated innovation facilitated by the integration of artificial intelligence (AI) in the design, development, and manufacturing processes of smart electric vehicles (SEVs). With sustainability and efficiency at the forefront of contemporary transportation initiatives, SEVs stand as a beacon of technological advancement, offering a paradigm shift towards eco-friendly mobility solutions. By harnessing the power of AI algorithms, SEVs are endowed with enhanced capabilities ranging from intelligent energy management systems to autonomous driving functionalities. This paper elucidates the intricate interplay between AI and SEV technologies, elucidating how AI-driven innovations propel the evolution of vehicle architecture, energy efficiency, safety protocols, and user experience. Moreover, it elucidates the transformative impact of AI on manufacturing methodologies, fostering agile production processes and adaptive manufacturing ecosystems. Through a comprehensive exploration of design principles, technological advancements, and manufacturing strategies, this paper seeks to elucidate the pivotal role of AI in accelerating innovation within the SEV domain. Furthermore, it underscores the broader implications of AI-enhanced SEVs on societal, economic, and environmental fronts, paving the way for a sustainable and intelligent transportation ecosystem. The current study pertains to the design and manufacture of the smart electric vehicle, which can automatically transfer the power from the internal system to the wheels and vice versa in a controlled way by the gyroscopic sensor and microcontroller. After doing controller based eV model for experimental purpose, the mechanical model of the system is designed using SOLIDWORKS software, the aim of the project is to create a smart car which automatically changes its power transmission.
Keywords: Automotive engineering; Gyroscopic sensor and microcontroller; Smart electric vehicles; SolidWorks; artificial intelligence